PENGETAHUAN DAN SIKAP PERAWAT TENTANG BASIC TRAUMA CARDIAC LIFE SUPPORT (BTCLS) DALAM PELAKSANAAN TINDAKAN KEGAWATDARURATAN DI RUANG KHUSUS RSUD Dr. M.M DUNDA LIMBOTO - Haslinda Damansyah; Susanti Monoarfa; Abdul Rahman Karim (Zaitun (Jurnal Ilmu Kesehatan), 2020)
Basic Trauma Cardiac Life Support (BTCLS) is the actions to provide first aid for victims of disasters or emergencies in order to prevent death or damage organs therefore their productivity can be maintained before a disaster or emergencies are occurs. The objective of research was to determine the relationship between Knowledge with Nurse Behavior about Basic Trauma Cardiac Life Support (BTCLS) in implementation emergency actions in special room of RSUD DR. M.M Dunda Limboto. The samples were 42 nurses with sampling technique used Total Sampling. Based on Chi Square test result significance α = 0,05, obtained ρ value 0,000 small than α = 0,05, which means there is relationship between Knowledge with Nurse Behavior about Basic Trauma Cardiac Life Support (BTCLS) in implementation emergency actions in special room of RSUD DR. M.M Dunda Limboto. The suggestion, these results of research are expected to be used as a reference for conducting first aid actions in emergency patients.